VALUE ANALYSIS INFORMATION SYSTEM TEST ON SENIOR HIGH SCHOOL PERGURUAN CIKINI - Dully Faisal; Haryanto Haryanto, SKom, MM (Jurnal Sistem Informasi, 1999)
Analysis of information systems is to understand the complex system and then makemodifications in several ways. The result of these modifications can form a newsubsystem or a new component or set of new transformations, in which the goal is toimprove the various functions of the system. To change the target system, change theoutput, achieve the same goal with another set of inputs or to make similarimprovements.The need for fast information systems analysis and accurate research is needed that isby the research literature and conduct field research data and information on therunning system.From results of this analysis is expected to produce an effective work processes andinefficient in terms of continuity of work processes of an organization or institution.